Corticomuscular Coherence Dependence on Body Side and Visual Feedback. (10th May 2022) - L'Abbate, Teresa; Armonaite, Karolina; Gianni, Eugenia; Bertoli, Massimo; Conti, Livio; Grifoni, Joy; Cancelli, Andrea; Cottone, Carlo; Trombetta, Elisabetta; Padalino, Matteo; Porcaro, Camillo; Tecchio, Franca
Graphical abstract: Highlights: Corticomuscular coherence (CMC) indexes neuronal synchronizations in motor control. CMC is not sensitive to manual dominance. CMC frequency and amplitude change when visual feedback lacks. Lack of visual feedback reduces the sensorimotor cortical involvement. Visual-dependent sensorimotor changes support that gaze is crucial in motor control. Abstract: Physiological movement develops on the basis of sensorimotor integration through synchronisation between the copy of signals sent to the effector muscles and the incoming flow of sensory information. Our aim is to study corticomuscular coherence (CMC), the most widely used measure of synchronization between brain and muscle electrical activities, in dependence on the level of visual feedback and the executing body side. We analysed CMC in 18 healthy volunteers while performing a weak isometric handgrip of an air bulb with either the right or the left hand, in either the presence or absence of visual feedback on the exerted pressure. The absence of visual feedback decreased the CMC peak frequency from 27 Hz to 23 Hz ( p  < 0.001), increased the CMC peak amplitude from 0.05 to 0.07 ( p  = 0.005) and decreased the electroencephalographic beta band power ( p  = 0.005). None of these measures changed in dependence on the performing hand ( p  > 0.2 consistently). The lack of dependence of CMC on the controlled hand involved in the movement can be considered in agreement with small hemispheric asymmetries of hand representations in primary sensorimotor cortices. Modulation of visual information changed corticomuscular synchronizations and cortical involvement, reflecting the crucial role of gaze in human behaviour. Given the fundamental role of sensory integration in motor execution, the availability of a simple index sensitive to modulations of perceptual afferents may prove useful in determining the use or the monitoring of the effects of sensory enrichments in personalized rehabilitation.